2021
DOI: 10.4317/medoral.24229
|View full text |Cite
|
Sign up to set email alerts
|

Maxillofacial trauma due to traffic accidents and falls: an exploratory study of associated factors

Abstract: Background This study aimed to determine the pattern of Maxillofacial trauma (MFT) due to traffic accidents and falls in a reference hospital in a rural region of northeastern Brazil between December 2011 and December 2018 and to identify associated factors. Material and Methods This was a cross-sectional study using 585 medical records of patients with MFT. The data were subjected to a Poisson-Tweedie multiple regression analysis to estimate the Prevalence ratio (PR), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 28 publications
0
13
0
1
Order By: Relevance
“…28,29 One study also suggested that falling strongly influenced the length of hospital stay and hospital costs for maxillofacial injuries. 6 Although potential factors associated with an increased risk of hospital admission have been previously examined for patients with oral and maxillofacial injuries caused by falling, no studies to date have determined the factors influencing long treatment durations. 3 Hirobe et al 30 analyzed the factors influencing the long-term hospitalization of cyclists and motorcyclists with oral and maxillofacial injuries.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…28,29 One study also suggested that falling strongly influenced the length of hospital stay and hospital costs for maxillofacial injuries. 6 Although potential factors associated with an increased risk of hospital admission have been previously examined for patients with oral and maxillofacial injuries caused by falling, no studies to date have determined the factors influencing long treatment durations. 3 Hirobe et al 30 analyzed the factors influencing the long-term hospitalization of cyclists and motorcyclists with oral and maxillofacial injuries.…”
Section: Discussionmentioning
confidence: 99%
“…Falling is the most common mechanism of unintentional injury, and the consequent oral and maxillofacial injuries have been extensively examined. 2,3,5,6,[9][10][11][12][13][14][15][16][17][18][19][20][21] Romeo et al 9 analyzed the characteristics of female patients with maxillofacial trauma in 14 maxillofacial surgery departments on 5 continents. They found that falling was the most common cause of maxillofacial trauma, followed by motor vehicle collisions and assault.…”
mentioning
confidence: 99%
“…Para os pacientes vítimas de acidentes de trânsito, o custo hospitalar total foi de R$ 150.635,56, com uma média de R$ 500,41 por paciente. Sobre a média de permanência de internação hospitalar entre todos os acidentados, observou-se uma permanência de 1,18 dias (gasto médio geral por internação de R$ 330,96) (Porto, Cavalcanti, Forte, 2021).…”
Section: Discussionunclassified
“…Studies have identified the commonest mechanisms of injury in the maxillofacial region as; motor vehicle and motorcycle collisions [ 12 , 13 , 14 ], assault [ 8 , 15 , 16 ], and falls [ 17 , 18 ]. Additionally, MI has been identified as one of the commonest forms of injury in gender-based violence [ 19 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%